2017
DOI: 10.1038/srep39956
|View full text |Cite
|
Sign up to set email alerts
|

Universal and reusable virus deactivation system for respiratory protection

Abstract: Aerosolized pathogens are a leading cause of respiratory infection and transmission. Currently used protective measures pose potential risk of primary/secondary infection and transmission. Here, we report the development of a universal, reusable virus deactivation system by functionalization of the main fibrous filtration unit of surgical mask with sodium chloride salt. The salt coating on the fiber surface dissolves upon exposure to virus aerosols and recrystallizes during drying, destroying the pathogens. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
153
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(162 citation statements)
references
References 36 publications
7
153
0
2
Order By: Relevance
“…‡ ‡ Related to this, Quan et al has reported that coating the fibres of a mask with salt can inactivate trapped viruses; they attribute this to the effect of osmotic up shock as aerosol droplets come into contact with and dissolve the deposited salt. 126 On the other hand, the possible role of osmotic down shock also deserves investigation. Enveloped viruses are found to be inactivated significantly faster in water than non-enveloped human enteric viruses.…”
Section: Forcesmentioning
confidence: 99%
“…‡ ‡ Related to this, Quan et al has reported that coating the fibres of a mask with salt can inactivate trapped viruses; they attribute this to the effect of osmotic up shock as aerosol droplets come into contact with and dissolve the deposited salt. 126 On the other hand, the possible role of osmotic down shock also deserves investigation. Enveloped viruses are found to be inactivated significantly faster in water than non-enveloped human enteric viruses.…”
Section: Forcesmentioning
confidence: 99%
“…Additionally, the dryness of the filter surface due to the NSS particles may have affected bacterial survival. Quan et al (2017) demonstrated that salt-coated filters are effective in deactivating virus bioaerosols [45]. The biggest difference between the aforementioned research and the current study is the fabrication process of antimicrobial filters.…”
Section: Antimicrobial Tests Of Nss-deposited Filters Using Bacterialmentioning
confidence: 73%
“…Sodium chloride (NaCl) also called 'table salt' as coating material on the fiber surface of the filtration unit of surgical mask effectively deactivated a number influenza virus species, suggesting a new strategy in the protective measures to avoid primary/secondary infection and transmission of many viruses, including SARS-CoV-19 (Quan et al, 2017). On the other hand, the natural adsorbents, including clay, charcoal, and clay minerals showed 99.99% adsorption of CoVs (Robson, 2020).…”
Section: Discussion: Challenges and Clinical Perspectives On Covid-19mentioning
confidence: 99%